Navigating Greenwashing: Exploring the Impact of Trust, Perceived Value, and Green Satisfaction on Brand Loyalty Towards Local Sustainable Cosmetic - Saputra, Dony; van den Broek, Matthijs; Marcelina, Nadia (Department of Management, Faculty of Economics and Business, Brawijaya University, 2024)
Across the globe, sustainability has become one of the biggest pushes for a flourishing beauty business. But some cautiously question to what extent greenwashing might be a problem among sustainable beauty brands, and how strong the consumer trust factor is. Specifically, this study aims to explore the effect of greenwashing, green trust, and perceived value on consumer brand loyalty among Generation Z mediated by green satisfaction on local cosmetics brands. A quantitative perspective research design using PLS-SEM analysis and distributed online among 246 local cosmetic product consumers was used in this research. This study reveals that greenwashing, green trust and perceived value produce both direct and indirect effects on brand loyalty through green satisfaction towards eco-friendly products. The study extends and fills the gap in the literature by furthering our understanding of brand loyalty in a sustainable beauty context by spotlighting greenwashing, trust, and perceived value as critical aspects.